Similar specificities of symbiont uptake by adults and larvae in an anemone model system for coral biology - Hambleton, Elizabeth A.; Guse, Annika; Pringle, John R. (The journal of experimental biology, 2014)
Reef-building corals depend for much of their energy on photosynthesis by symbiotic dinoflagellate algae (genus Symbiodinium) that live within their gastrodermal cells. However, the cellular mechanisms underpinning this ecologically critical symbiosis, including those governing the specificity of symbiont uptake by the host, remain poorly understood, in part because of the difficulties of working with corals in the laboratory. Here, we used the small symbiotic sea anemone Aiptasia as an experimentally tractable model system to analyze the specificity and timing of symbiosis onset in larval and adult animals under controlled laboratory conditions. Using four clonal, axenic Symbiodinium strains, we found no difference in uptake specificity between larvae (even when very young) and adults. Although both compatible and incompatible algal strains were found within the larval guts, only the former appeared to be internalized by gastrodermal cells, and they (but not incompatible algae) proliferated rapidly within the larvae in the absence of detectable exchange with other larvae. Older larvae showed reduced ingestion of both compatible and incompatible algae, and the addition of food failed to promote the uptake of an incompatible algal strain. Thus, Aiptasia adults and larvae appear to have similar mechanisms for discriminating between compatible and incompatible dinoflagellate types prior to phagocytosis by host gastrodermal cells. Whether a particular algal strain is compatible or incompatible appears to be stable during years of axenic culture in the absence of a host. These studies provide a foundation for future analyses of the mechanisms of symbiont-uptake specificity in this emerging model system.